Physiological and Biochemical Responses of Iranian Alfalfa (Medicago sativa L.) Ecotypes to Salt Stress - Torabi, Masoud (2010)
Salinity is one of the world‟s most serious environmental problems in agriculture where one-third of the world‟s cultivated land is affected by salt stress. The physiological and biochemical processes of plants can be related to the deleterious influences of salt on plants. The breeding techniques and conventional selection that is based on differences in agronomic characters could not cover all responses of plants to salt stress, because those agronomic characters represent the combined genetic and environmental effects on plant growth. To identify some salt tolerant ecotypes from its centre of origin in Iran, a study was conducted on the physiological and biochemical responses of genotypes of alfalfa to salt stress at three stages of plant development namely, germination, seedling growth, and mature plant growth. At the germination stage, nineteen ecotypes of alfalfa collected in August 2007 from Iran were evaluated for their salt tolerance based on seed germination parameters in response to different salinity levels. Seeds were germinated with distilled water (control), or 50, 100, 150, 200, 250 mM of NaCl solution (equivalent to 0, 5, 10, 15, 20 and 25 dS/m, respectively). Results showed that there were significant effects of salinity levels, ecotypes, and interaction between salinity and ecotype on germination rates,germination speed and germination index. There was a wide range of salt tolerance between the ecotypes. Ecotypes originating from the arid (Bami) and cold areas (Galehbani) were more tolerant than other areas where the germination percentage for Bami and Galehbani respectively was 86% and 78%. At the seedling stage 20 Iranian alfalfa ecotypes were planted in a hydroponic system in the greenhouse. After 8 days when seedlings had reached the first trifoliate leaf stage the electrical conductivity (EC)of nutrient solution was increased by adding sodium chloride gradually to 15 dS/m. The results showed differences in response of ecotypes to salinity in terms of root and shoot biomass and proline concentration. Shoots were more affected by salinity than roots. Free proline increased with salinity in all ecotypes. Based on germination and seedling performance the ecotypes that were relatively salt tolerant were Shorkat, Rehnani, Mohajeran, Ghargholough and Nik-Shahri and these were chosen for the next phase of study. The five selected ecotypes were planted in polybags filled with sand and immersed in nutrient solution. After 2 months every 15 days the EC was increased by 3 dS/m, and the final EC was 18 dS/m. At each stage of salinity (6, 12, and 18 dS/m) the physiological characteristics of alfalfa ecotypes were measured. The results showed that physiological parameters were affected by salt concentration. Salt stress had a negative impact on CGR in all ecotypes and there were differences in response of CGR to salinity between ecotypes. Salt stress resulted in a linear decline in the photosynthetic rate. There was a positive correlation between CO2 net uptake and stomatal conductance. The chlorophyll content decreased with increasing salinity but there was no significant difference between ecotypes in terms of chlorophyll content. The results of Fv/Fm ratio showed that up to 12 dS/m there was no significant change in Fv/Fm ratio but after 12 ds/s the Fv/Fm ratio decreased with increasing of salt stress. Salt stress also affected the concentration of Na+, Cl-, N, K but the concentration of P was not significantly affected by salinity levels. The P, and K+ concentration were not significantly different between ecotypes but Na+, Cl-, and N, were significantly different between the ecotypes. In terms of physiological response to salt stress the ecotype Gharghologh in this study was identified as the most tolerant ecotype. To characterize biochemical responses of five Iranian alfalfa ecotypes to salt stress, biochemical components measured were: root soluble sugars (fructose, glucose, and sucrose), free proline, and total amino acids. The results indicated that the levels of sugars in root increased when the mature alfalfa plant was exposed to salt stress but the increase in monosaccharides was greater than disaccharides. With increasing salt stress the concentration of free proline was elevated but differences in rate of proline increase were observed between ecotypes. There were differences between amino acids in their response to salt stress. The concentration of three amino acids, proline, threonine, and lysine increased with salt stress but all other amino acids declined with salt stress. This may indicate that threonine and lysine may play the same role as proline in mitigating the effects of salt stress. The response of ecotypes to salt stress in terms of changes in amino acids was significantly different where ecotype Gharghologh showed higher levels amino acids under salt stress. Based on results of physiological and biochemical responses of alfalfa ecotypes under salt stress it was found that the ecotypes Gharghologh and Nik-Shahri were the most tolerant among the 20 ecotypes